Production spillovers: Are they valued? - Joseph Price (IZA World of Labor, 2017)
Workers can contribute to total firm production directly through their own output or indirectly through their influence on the output of co-workers. Workers with positive productivity spillover effects cause individuals around them to perform better and increase overall team production. In contrast to the “peer effects” literature, workers with positive productivity spillovers may not be the workers with the highest levels of personal output. Such productivity spillovers are important for team success even though they play only a minor role in determining worker pay.
Keywords: J24; J30; 330; production spillovers; marginal revenue product; team performance